Causas de la politización reactiva del conservadurismo evangélico en el Perú contemporáneo - Tello, Kevin (2019)
For much of the 20th century, Evangelical churches were a religious sector traditionally resistant to political participation. However, nowadays, they participate in public life and are key actors in certain political junctures due to their capacity to convene, mobilize and pressure. Faced with this scenario, this article aims to identify and explain the factors that allow us to understand the reactive politicization of Evangelical churches. For this, in-depth semi-structured interviews were conducted with key actors and scholars, and different secondary sources were reviewed to trace the process and provide an explanation for this phenomenon. The general hypothesis that guides the analysis is that Evangelical churches gave up to their traditional resistance to political participation and dabbled in politics through social mobilization due to the confluence of three factors: the neopentecostalization of Evangelical churches, the influence of the American Christian Right and the Peruvian state’s responses to the demands of the feminist and LGBT movements.